Piranha - Cussler, Clive (Cussler, Clive. Oregon files adventures., 2015)
During a covert operation, Cabrillo and the crew meticulously fake the sinking of the Oregon--but when an unknown adversary tracks them down despite their planning and attempts to assassinate them, Cabrillo and his team struggle to fight back against an enemy who seems to be able to anticipate their every move.